A cross-sectional analysis of the relationship between ischemic stroke and uric acid in young people in highland areas - Yang, Yifan; Gao, Li; Shen, Fuwei; Miao, Jiaodan; Liu, Hua (Frontiers in Endocrinology, 2024)
Objective To investigate the relationship between serum uric acid (SUA) levels and ischemic stroke in young patients in the Ganzi Tibetan plateau area. Methods A cross-sectional survey was undertaken from January 2020 to June 2023 involving young patients (age: 15–45 years) diagnosed with ischemic stroke. The survey was conducted at the Department of Internal Medicine of the People's Hospital of Derong County, Ganzi Prefecture. The participants underwent a comprehensive assessment, including questionnaire surveys, physical examinations, laboratory tests, and head computed tomography (CT) examinations. Based on the tertiles of serum uric acid (SUA) levels, the patients were stratified into three groups. Furthermore, stroke severity was classified into mild (1–4 points), moderate (5–15 points), and severe (>15 points) categories using the National Institute of Health Stroke Scale. Results The severe stroke group exhibited higher levels of age, glucose, systolic blood pressure, serum triglyceride, low-density lipoprotein cholesterol, and serum uric acid (SUA) compared to the mild stroke group (P < 0.05). Furthermore, the likelihood of male sex, advanced age, smoking, and a family history of stroke, diabetes mellitus, and heart disease were significantly elevated in the severe stroke group compared to the moderate stroke group (P < 0.05). Multivariate logistic regression analysis conducted on young adults residing in highland areas revealed a significant association between SUA levels and the risk of stroke. Conclusion Elevated SUA levels serve as a distinct risk factor for the development of a major stroke in young patients in highland areas. At SUA levels of 320.56 mol/L, the risk of a moderate-to-severe stroke is noticeably elevated.